Role of phytohormones and secondary metabolites in mitigating stressors of selected crop plants - Karigidi, Mojisola Esther; Fakunle, Oluwalonimi Ewaoluwa; Adeyanju, Anne Adebukola; Karigidi, Kayode Olayele (Journal of Plant Stress Physiology, 2025)
Crop plants are continuously threatened as climate change imposes abiotic stressors that limit crop growth and yield. Abiotic stress includes drought, high salt concentration and excessive heat. Phytohormones which act as messengers, play a central part in coordinating adaptive responses to these environmental stressors. Plants often employ phytohormones, such as cytokinins (CKs), auxins (AUX), ethylene (ET), salicylic acid (SA), jasmonic acid (JA), abscisic acid (ABA), brassinosteroids (BRs) and gibberellins (GAs), in their strategic response to stress. The review of original research works in the last ten years specifically highlights the involvement of plant hormones in enabling some crop plants to withstand environmental stressors. This study explored the active roles of secondary metabolites, which are by-products of plant metabolism in conferring stress tolerance on crop plants. These secondary metabolites are flavonoids and phenolic compounds that act as antioxidants, scavenging reactive oxygen and nitrogen species thereby protecting plant cells from oxidative damage during stress. The phytohormonal signaling and secondary metabolite production enhance crop plants’ overall stress tolerance and adaptation to harsh environmental conditions. We provide a summary of studies from 2014 to 2024 reporting the ability of these phytochemicals to mitigate the effects of climate-induced stressors.